Kajian Efektivitas dan Efisiensi Pemanfaatan Limbah Batu Bara dalam Pembuatan Paving block Ramah Lingkungan - erliana, hilma; Dwinta, Ade (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
The waste from the operation activities of the Nagan Raya 1-2 Power Plant (PLTU) has caused environmental pollution. Therefore, this research was conducted to find a solution on how to directly reduce the environmental pollution load due to the accumulation of solid waste in the form of fly ash. This was achieved by conducting a technical and economic analysis to obtain the effectiveness and efficiency values of producing environmentally friendly paving blocks. The results showed that in terms of technical analysis, the highest water absorption percentage occurred in the composition with 25% fly ash, which was 10.73%, followed by compositions with 20%, 15%, 10%, and 5% fly ash, which had absorption percentages of 10.30%, 9.69%, 9.40%, and 8.60%, respectively. According to the SNI 03-0692-1996 standard, the maximum water absorption for paving blocks of quality grade D is 10%. In terms of economic analysis, the highest cost was incurred with a composition of 0% fly ash, which was Rp. 2,565.00, followed by compositions with 5%, 10%, and 15% fly ash, which had costs of Rp. 2,516.00, Rp. 2,468.00, and Rp. 2,420.00, respectively. Therefore, it can be concluded that the composition with 15% fly ash meets the effectiveness and efficiency criteria in both technical and economic aspects. Keywords: Fly ash, technical analysis, economic analysis